Sepse em pacientes com lesão renal aguda severa - Inácio, Ana Cristina Rocha (2017)
The main causes of mortality among critical patients are severe sepsi s and septic shock. They have a negative and growing impact on public health. Acute renal injury (AKI) is common during the critical phase of the disease, there is an increased incidence in hospitalized patients and indicates a worsening of clinical outcome. It is associated with increased use of intensive resources, mortality and increased length of hospital stay. Sepsis and AKI are increasing among critically ill patients and pose a higher risk of morbidity and mortality. Being established sepsis as a key factor for the development of AKI in critical illness. We aimed to analyze the prevalence of sepsis in patients with acute renal injury submitted to hemodialysis renal replacement therapy. The study evaluated 44 patients over 18 years of age who started hemodialytic renal replacement therapy in the intensive care unit of a large tertiary hospital, a reference in the Triângulo-Norte macro region of the state of Minas Gerais, Brazil. There was an analysis of patient records and the Hospital Information System (SIH), such as age, gender, date of hospital stay, date of hospitalization in the Intensive Care Unit (ICU), diagnosis of hospitalization, biochemical and hematological parameters, existing. Hemodialysis therapy, norepinephrine use, hospital discharge or death date, biochemical and hematological parameters, infections after hemodialysis was started were collected. Data collection was done through the completion of a questionnaire based on the proposed objectives. The data were evaluated by descriptive measures and tables. Quantitative variables were evaluated using the Shapiro-Wilk test. For the quantitative variables that follow normal distribution the Pearson correlation coefficient was calculated and those variables that do not follow normal distribution were obtained Spearman correlation coefficient. The association of qualitative variables was assessed by the chi -square test. The variables were still evaluated using Student's t-test or Kruskall-Wallis test. The socio-demographic variables were analyzed revealing that 63.6% were males with a mean age of 63.3 years. Sepsis was the main cause of acute renal injury in 65.9% of patients and mortality was 79.5%. The length of ICU stay was 22.45 ± 13.5 days and the total hospitalization time was 31.30 ± 21.4 days. Intermittent hemodialysis was the most used in 61.4% of the cases. Septic shock and severe sepsis were present in 54.5% and 13.6% of the population. The main focus of primary infection was pulmonary 41.1%. Despite international campaigns, sepsis and its mortality remain high. Preventing the onset of infections should be avoided by avoiding their evolution to more severe forms.